Correlation of hepatitis C RNA and serum alanine aminotransferase in hepatitis B and C seronegative healthy blood donors - Ali Natasha; Moiz Bushra; Moatter Tariq; Ahmed Shiraz; Adil Salman; Khurshid Mohammad (Wolters Kluwer Medknow Publications, 2010)
Introduction: Historically, serum alanine transaminase (ALT) has been used as a surrogate marker in the detection of hepatitis viruses in blood donors. With the availability of newer sensitive technologies for the detection of seroconversion, the value of ALT becomes questionable but continues to be used for this purpose with subsequent discarding of ALT elevated blood units. Objective: The present study aims to evaluate the significance and cost effectiveness of ALT as a surrogate marker for hepatitis C virus infection in healthy asymptomatic blood donors who were serologically negative. Materials and Methods: The study was conducted at clinical laboratory of a tertiary care hospital for a period of one year from November 2006 to October 2007. All donors were screened serologically for hepatitis B, C and HIV I and II, syphilis and malaria and those tested positive were excluded from further evaluation. Gender-wise reference ranges and minimal and markedly raised results for ALT (described respectively as one and two folds increase above reference range) were defined and, accordingly, donors were grouped into three. Two hundred seronegative blood donors were randomly selected from all three groups of ALT results and tested for hepatitis C nucleic acid through Amplicor; HCV RNA test. The cost of discarding an ALT -only elevated blood unit was also assessed. During the study period, 25117 subjects donated blood. Eight hundred and Results: seventy two donors (3.4%) were positive for one or more serological tests. ALT of all donors ranged from 0-1501 U/L (Mean ± SD; 33.4 ± 25.45U/L). The donors seronegative for all disease markers were 24245 (96.6%). Of these, 21164 (87.2%) donors had their ALT within reference range while 2874 (11.8%) and 207 (0.8%) of donors had minimal and markedly elevated results. Thus, 621 blood bags (red cells, platelets and plasma) costing $ 39200.0 were discarded based on ALT results alone. Of 200 seronegative donors evaluated for hepatitis C nucleic acid, only one within markedly elevated ALT levels was found to be positive. The present work did not support a positive association between hepatitis C virus nucleic acid and elevated ALT in healthy serologically negative blood donors. Conclusion: We did not find serum ALT testing in donors as cost effective strategy for detection of hepatitis C virus ribonucleic acid. As the number of samples tested by us was small we suggest further work to evaluate the value of ALT levels in serologically negative donors in association with hepatitis C antigen and NAT testing to elucidate the true burden of disease in geographical regions where hepatitis C is endemic and voluntary blood donation is sparse.